THE EFFECTIVENESS OF COGNITIVE BEHAVIOR THERAPY IN REDUCING THE LEVEL OF ANXIETY FACING DEATH IN THE ELDERLY - Latuheru, Grace (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
Death anxiety is a feeling of discomfort and discomfort or fear caused by the perception of a real threat or imagining the threat of someone's existence The consequences that someone who experiences this disorder will receive are difficulty sleeping at night, usually only sleeping if it is dawn and anxiety when hearing the news of death from the closest person. In this study, researchers used a research method, namely this single subject experimental method is with CBT therapy in order to change negative thoughts into positive ones. The subject in this study amounted to 1 person who showed comprehensive anxiety symptoms, especially towards death. The subject's age is 60 years. Subjects were taken based on symptoms or symptoms obtained from observations and interviews. Data collection techniques using observation, interviews. The intervention carried out is cognitive behavior therapy to reduce anxiety about facing death. After the provision of therapy, the subject told in detail about the fears he experienced, because in recent years he had lost his closest person. The subject was made aware of changing irrational thoughts to rational ones. The client was also given progressive relaxation therapy to reduce his anxiety. After being given, the client claimed to be weak and sleepy. The client became more relaxed and could return to normal activities.